Pemimpin Perempuan dan Non-Muslim Perspektif Ulama Tiga Serangkai - M. Jamil; Ja'far Ja'far (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
The issue of women’s and non-Muslim’s leadership seems to be unrestrained in the Islamic world. In Indonesia, the Islamic liberal groups or the modernists will usually accept women or non-Muslim for being the Muslim community leader. In contrast, the Muslim traditionalists and radical groups will usually show their firm rejection. This study seeks to elaborate the thought of the three Muslim scholars in the Eastern Sumatera, i.e., Abdul Halim Hasan, Zainal Arifin Abbas, and Abdur Rahim Haitami, about the leadership of women and non-Muslim. The article will put the position of thought of these scholars among the discourse of the issue. Employing content analytical method, the study finds that the three scholars reject women and non-Muslim for being a leader, especially a state leader, of the Muslim community. They argue that leadership is a privilege honored to men, not to a woman. They also assert that the principle foundation of the sharī’a forbids the Muslims from designating non-Muslim as their leader, except within emergency conditions. Although these three Muslim scholars have been mostly influenced by modern thought, they hardly accept women’s and non-Muslim’s leadership. Therefore, the ideas they propose will contradict the ideas held by the liberal Muslim groups or other proponents of democracy.